Picky Eating Behaviors Linked to Inappropriate Caregiver-Child Interaction, Caregiver Intervention, and Impaired General Development in Children - Hsun-Chin Chao; Hsueh-Ling Chang (Elsevier, 2017)
To investigate the differences in eating behaviors between picky and nonpicky eaters, and to correlate parental management of children's eating problems with qualities of general development in children. Methods: This was a cross-sectional analysis of parental observations on their children's eating behavior, sampled from three major cities in Taiwan. We used a structured questionnaire during face-to-face interviews to collect information on each child's picky eating habits and behaviors, caregiver-child interaction and intervention during feeding, and the child's qualities of general development. Analysis of variance was used to determine significant differences between picky and nonpicky eaters. Results: Sixty-two percent of the children were considered to be picky eaters. Lack of appropriate caregiver-child interactions (e.g., repeated food attempt, persuasion, and encouragement) and the presence of inappropriate parental interactions (e.g., threatening, snacking, and nutrient supplementation) were significantly more common in picky eaters. Picky eaters also tended to exhibit low development quality in the domains of learning ability, interpersonal relationships, and physical performance, particularly in their attention span and uncooperativeness. Conclusion: There is a relationship between inappropriate parental interaction and interventions in children's eating problems and the low quality of general development in picky eaters.